2017
DOI: 10.7869/djo.271
|View full text |Cite
|
Sign up to set email alerts
|

National Programme for Control of Blindness (NPCB) in the 12th Five year plan: An Overview

Abstract: National Programme for Control of Blindness (NPCB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Diabetic retinopathy (DR) is a microvascular complication of DM and can cause blindness or visual impairment (VI). Although cataract remains a principal cause of blindness in India, other retinal causes (especially DR) are emerging as priority diseases for national programme for control of blindness (NPCB)10 as well as vision 2020 India 11. Prevalence of DR among diabetics has been reported to be 9.6%–21.7% in various studies conducted across India over the last decade 12–16.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic retinopathy (DR) is a microvascular complication of DM and can cause blindness or visual impairment (VI). Although cataract remains a principal cause of blindness in India, other retinal causes (especially DR) are emerging as priority diseases for national programme for control of blindness (NPCB)10 as well as vision 2020 India 11. Prevalence of DR among diabetics has been reported to be 9.6%–21.7% in various studies conducted across India over the last decade 12–16.…”
Section: Introductionmentioning
confidence: 99%
“…However, the screening of patients is still carried out in rural areas. 5 Good visual outcome is achievable in outreach eye camp under standard conditions. 13 Over the past decade, manual Small Incision Cataract Surgery (SICS) has become an established surgical alternative to phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
“…4 According to National Programme for Control of Blindness, which was launched in the year 1976 as a 100% centrally sponsored scheme with the goal to reduce the prevalence of blindness from 1.4% to 0.3% states that cause of blindness because of cataract in India is as high as 62%. 5 Also, a combined survey done by WHO-NPCB from 1986-1989 concluded that major cause of blindness in India is cataract about 80.1%. 6 The treatment for cataract is surgical, a highly cost-effective intervention with excellent prognosis for sight restoration.…”
Section: Introductionmentioning
confidence: 99%
“…Of these 6.8 million, around 1 million people are corneal blind bilaterally. 4 The first eye bank in India was started by Muthiah in 1948 and he performed the first successful corneal transplant in India. 5 Now, after 70 years of the establishment of the concept of eye bank, the patients who are waiting for corneal transplant still constitute a major backlog in the society.…”
Section: Introductionmentioning
confidence: 99%